Femoroacetabular impingement after the femoral neck fracture healed in a nonanatomical position - mladenovic, marko desimir; micic, ivan; Milenkovic, Sasa; Stoijiljkovic, Predrag; Barjaktarović, Radoslav (Vojnosanitetski pregled, 2021)
Abstract Introduction. Femoroacetabular impingement is the result of the pathological conditions in the osseous acetabulum and/or the proximal femur. One of its causes is a non-anatomically healed femoral neck fracture. Case report. A male, aged 51, with a subcapital left femoral neck fracture was treated conservatively. The fracture healed 9 months later and although the patient was walking on crutches he suffered from pain in the left groin. The X-ray images showed the valgus and the retroposition of the left femoral head. The patient was operated on and intraoperatively the thickness and a bone prominence in the anterosuperior femoral neck area in the line of the previous fracture were found, which was pressing and spreading beneath the acetabular labrum, thus squeezing the acetabular cartilage. The labrum lesion which was found was the result of the mechanical pressure of the existing femoral neck deformity during the hip movements. Irretrievably damaged part of the labrum was resected and the anterosuperior femoral head-neck osteochondroplasty was done. One year after the surgery, the patient had no pain, he walked without limping, the impingement test was negative, the radiological parameters were adjusted and there were no signs of the avascular necrosis of the femoral head. Conclusion. The femoral neck fracture should be treated adequately with the full anatomical position and the proper internal fixation. If the deformity occurs as the result of a treatment, it should be removed as soon as possible to prevent the osteoarthritis of the hip.